1972
DOI: 10.1042/bj1290937
|View full text |Cite
|
Sign up to set email alerts
|

Effects of safrole and isosafrole pretreatment on N- and ring-hydroxylation of 2-acetamidofluorene by the rat and hamster

Abstract: 1. The effects of safrole and isosafrole pretreatment on both N- and ring-hydroxylation of 2-acetamidofluorene were studied in male rats and hamsters. 2. Isosafrole (100mg/day per kg body wt.) pretreatment of rats for 3 days did not have any effect on urinary excretion of hydroxy metabolites of 2-acetamidofluorene. However, similar pretreatment with safrole produced increased urinary excretion of N-, 3- and 5-hydroxy derivatives. 3. Similar treatment with these two chemicals for 3 days increased ring-hydroxyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

1973
1973
1997
1997

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(2 citation statements)
references
References 14 publications
2
0
0
Order By: Relevance
“…The present results, of severalfold increase in Nhydroxylation without similar increase in ringhydroxylation of 2-acetamidofluorene by liver microsomal fractions from hamsters after 3-methylcholanthrene pretreatment (Table 1), are in agreement with our previous data (Lotlikar et al, 1967;Lotlikar & Wasserman, 1972) and with those reported by .…”
Section: Resultssupporting
confidence: 94%
“…The present results, of severalfold increase in Nhydroxylation without similar increase in ringhydroxylation of 2-acetamidofluorene by liver microsomal fractions from hamsters after 3-methylcholanthrene pretreatment (Table 1), are in agreement with our previous data (Lotlikar et al, 1967;Lotlikar & Wasserman, 1972) and with those reported by .…”
Section: Resultssupporting
confidence: 94%
“…N-Hydroxylation of 2-acetamidofluorene by liver microsomal fractions was increased severalfold when hamsters were pretreated with 3-methylcholanthrene (Table 2). Data on the increase in Nhydroxylation are in agreement with our previous data (Lotlikar et al, 1967;Lotlikar & Wasserman, 1972) and with those reported by . Arrhenius (1968Arrhenius ( , 1969 suggested that the mixed-function amine oxidase which oxidized NN-dimethylaniline to its N-oxide was also responsible for N-oxidation of carcinogenic aromatic amines and amides.…”
Section: Resultssupporting
confidence: 93%